Educational Games to Sharpen Children's Fine Motor Skills - Yusuf Hadi Putra, Muhammad (Sekolah Tinggi Agama Islam Kuningan, 2024)
Background: Fine motor skills are a fundamental component of early childhood development, significantly influencing academic readiness and daily life functioning. Despite their importance, effective and contextually appropriate interventions to enhance fine motor development in preschoolers require further exploration, particularly through structured educational play approaches.Objective: This study aims to investigate the effectiveness of educational play as an intervention to improve fine motor skills in preschool children aged 4–6 years.Method: The study employed a qualitative design using a 12-week case study approach involving 24–30 preschoolers from 3–4 early childhood education centers.Findings and Implications: Results showed that manipulative play significantly improved fine motor coordination, with activity completion time decreasing from 4.8 minutes to 1.4 minutes and precision increasing from 62% to 94%. Creative play enhanced visual-motor integration, demonstrated by a shift in pencil grip from palm/cylindrical dominance (78%) to dynamic tripod (71%), and improved scissors accuracy from 38% to 88%. Technology-based games effectively supported digital skills but were limited in promoting 3D object manipulation and tactile feedback. Skill sustainability remained strong at follow-up, with scores increasing from 8.35/10 to 8.40/10 and showing substantial transfer to academic domains (r = 0.78). Conclusion: A balanced integration of manipulative, creative, and technology-based educational play constitutes an effective intervention for enhancing fine motor skills and supporting the holistic development of preschool children.